Impact of PIK3CA gain and PTEN loss on mantle cell lymphoma biology and sensitivity to targeted therapies - Bettazova, Nardjas; Senavova, Jana; Kupcova, Kristyna; Sovilj, Dana; Rajmonova, Anezka; Andera, Ladislav; Svobodova, Karla; Berkova, Adela; Zemanova, Zuzana; Daumova, Lenka; Herman, Vaclav; Dolníkova, Alexandra; et al. (Blood advances, 2024)
Besides many other mutations in known cancer driver genes, mantle cell lymphoma (MCL) is characterized by recurrent genetic alterations of important regulators of the phosphoinositol-3-kinase (PI3K) cascade including PIK3CA gains and PTEN losses. To evaluate the biological and functional consequences of these aberrations in MCL, we have introduced transgenic expression of PIK3CA (PIK3CA UP) and performed knockout/knockdown of PTEN gene (PTEN KO/KD) in 5 MCL cell lines. The modified cell lines were tested for associated phenotypes including dependence on upstream B-cell receptor (BCR) signaling (by an additional BCR knockout). PIK3CA overexpression decreased the dependence of the tested MCL on prosurvival signaling from BCR, decreased levels of oxidative phosphorylation, and increased resistance to 2-deoxy-glucose, a glycolysis inhibitor. Unchanged protein kinase B (AKT) phosphorylation status and unchanged sensitivity to a battery of PI3K inhibitors suggested that PIK3CA gain might affect MCL cells in AKT-independent manner. PTEN KO was associated with a more distinct phenotype: AKT hyperphosphorylation and overactivation, increased resistance to multiple inhibitors (most of the tested PI3K inhibitors, Bruton tyrosine kinase inhibitor ibrutinib, and BCL2 inhibitor venetoclax), increased glycolytic rates with resistance to 2-deoxy-glucose, and significantly decreased dependence on prosurvival BCR signaling. Our results suggest that the frequent aberrations of the PI3K pathway may rewire associated signaling with lower dependence on BCR signaling, better metabolic and hypoxic adaptation, and targeted therapy resistance in MCL.
Keywords: Drug Resistance, Neoplasm; fosfatidylinositol-3-kinasy třídy I; signální transdukce; cílená molekulární terapie; Phosphatidylinositol 3-Kinases; nádorové buněčné linie; Cell Line, Tumor; Class I Phosphatidylinositol 3-Kinases; fosfatidylinositol-3-kinasy; lidé; Signal Transduction; Proto-Oncogene Proteins c-akt; Humans; lymfom z plášťových buněk; PTEN Phosphohydrolase; chemorezistence; fosfohydroláza PTEN; Receptors, Antigen, B-Cell; Lymphoma, Mantle-Cell; protoonkogenní proteiny c-akt; receptory antigenů B-buněk; Molecular Targeted Therapy